Effect of Back Massage on the Intensity of Labor Pain - Inayatul Aini; Dhita Yuniar Kristianingrum; Kiftiyah (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2022)
Labor is the process of expulsion of the fetus the uterus through the birth canal. Every woman labor must experience labor pain. Labor pain is physiological because it is caused by uterine distension and cervical dilation. Based on a preliminary study among 6 women in labor, 100% of respondents experienced pain, 33.3% of respondents responded to the pain by grinning and hissing, and were able to follow orders provided by healthcare workers well. 50% of respondents responded to pain by shouting, crying, and sometimes were able to follow orders provided by healthcare workers. Furthermore, 16.7% of respondents responded to pain by crying hysterically, screaming and pulling nearby objects. This study aims to analyze the effect of back massage in reducing pain intensity during the active phase of the first stage labor. This was a pre-experimental study with a pretest post-test one group design. Data were collected using an observation sheet. Study samples were primiparous and multiparous women in the active phase of the first stage of labor (20) at Private Practice Midwife of Mrs.